Analisis Pengaruh Budaya Organisasi, Gaya Kepemimpinan Dan Sistem Kompensasi Terhadap Kinerja Karyawan Pt Luar Biasa Teknologi - Ulrikus Marung, Ulrikus Marung (Universitas Serang Raya, 2024)
This study aims to determine the Influence of Organizational Culture, Leadership Style, and Compensation System on Employee Performance. This research was conducted on employees of PT Luar Luar Teknologi. The respondents of this study were all employees of PT Luar Luar Teknologi, totaling 35 people using questionnaires as a data collection technique. The SPSS program is used for data analysis through three stages of testing: descriptive statistics, classical assumption test and hypothesis test. The results of the analysis showed that Organizational Culture (X1), Leadership Style, and Compensation System have positive non-standardized coefficients which are 0.141, 0.508, and 0.374 respectively. Coefficient standardization shows that Leadership Style has the most significant impact on employee performance with a beta coefficient value of 0.502, followed by the Compensation System with a beta coefficient value of 0.427, and Organizational Culture with a beta coefficient value of 0.241. Statistically significant T-values show that these three independent variables have a significant influence on employee performance. In addition, all Sig. values (significance) associated with the independent variable were less than a significance level of 0.05, indicating that the relationship between the independent variable and employee performance was statistically significant. This provides a deeper understanding for company management in designing policies and strategies to improve employee performance. In addition, low significance values indicate that these results could not have happened by chance, reinforcing the belief that the relationship between the independent variable and employee performance is statistically valid